Investigating the role of NPR1 in dilated cardiomyopathy and its potential as a therapeutic target for glucocorticoid therapy - Huang, Yaomeng; Li, Tongxin; Gao, Shichao; Li, Shuyu; Zhu, Xiaoran; Li, Ying; Liu, Dangyang; Li, Weimin; Yang, Linquan; Liu, Kunshen; Zhang, Zheng; Liu, Chao (Frontiers in Pharmacology, 2023)
In the present study, natriuretic peptide receptor 1 (NPR1) was identified as a core gene associated with dilated cardiomyopathy (DCM) through bioinformatics analysis (weighted gene co-expression network analysis [WGCNA] and Single-sample gene set enrichment analysis [ssGSEA]), and a strong correlation with DCM was observed. The results of basic experiments showed a significant impairment of cardiac and renal function in patients with DCM and in rats, accompanied by a notable decrease in NPR1 expression. Symptoms of DCM were evident in NPR1 knockout (KO) mice, indicating a meaningful role for NPR1 in the development of DCM. Furthermore, glucocorticoids significantly improved cardiac and renal function and upregulated the expression of NPR1 in patients with DCM and in rats. These results suggest an important role of NPR1 in the pathophysiology of DCM and its potential as a crucial target for glucocorticoid treatment of DCM. This study provides a theoretical and experimental basis for the further exploration of DCM pathogenesis and the search for treatment methods.